Penerapan Metode Ceramah dalam Meningkatkan Pemahaman Materi Sejarah Turki Usmani Kelas VIII di SMPN 1 Telagasari - Agnia Rahma Farhillah; Ahmat Sifaul Anam; Ananda Bagus; Arum Anastasya; Dhea Khoerunisa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to evaluate the effectiveness of using the lecture method to enhance students’ comprehension of Ottoman Turkish History in class VIII at SMPN 1 Telagasari. The primary issue identified is the students' low grasp of historical content, which tends to be chronological and information-heavy. The study adopts a Classroom Action Research (CAR) approach, conducted in two cycles, each comprising planning, action implementation, observation, and reflection phases. Data collection was done using a 20-item multiple-choice test and analyzed quantitatively. Findings revealed that only 10% of students passed in the pre-cycle with an average score of 25, increasing to 40% in the first cycle with an average score of 35, and reaching 45% in the second cycle with an average score of 45. Despite the incremental improvements, the outcomes did not meet the minimum success criteria (≥75% of students achieving the passing score). This indicates that the lecture method alone has limitations in significantly enhancing students’ understanding unless integrated with more interactive teaching strategies.